Ethical issues regarding machine(-assisted) translation of literary texts. - Taivalkoski-Shilov, Kristiina (Perspectives: Studies in Translatology, 2019)
This article investigates essential ethical issues that should be taken into consideration when adopting or tailoring technological tools for literary translation. The discussion on ethical issues draws on recent studies on translation technology and on the usage of machine(-assisted) translation for literary language. An overview of the consequences of the recent increase in technologization for both non-literary and literary translation is provided and an argument for sustainable development in literary translation is made, based on a holistic understanding of translation quality. The notion of voice is taken as an example of the special challenges related to the translation of literary language, which research on machine(-assisted) translation of literary language has not yet sufficiently taken into account. Lastly, avant-garde aesthetic views and usages of machine translation are presented through the notion of noise.